Evaluating electronic medical records in inpatient psychiatric services using the PIECES framework - Mayasqa, Nur Aini; Pamungkas, Canggih Ajika (Science Midwifery, 2025)
This study evaluated the implementation of Electronic Medical Records (EMR) in inpatient psychiatric services at RSJ Mutiara Sukma using the PIECES framework. Employing a qualitative approach, data were collected through in-depth interviews and observations involving twelve informants from various healthcare professions. Thematic analysis identified systemic challenges across six domains: performance, information, economy, control, efficiency, and service. Key issues included slow system response times, fragmented data presentation, dual documentation, limited audit trails, inefficient workflows, and gaps in user training. Despite having an EMR infrastructure, its utilization remained suboptimal due to usability and integration barriers. The study underscores the need for user-centered design, continuous training, and institutional support to optimize EMR systems in psychiatric settings. These insights are essential for enhancing digital health strategies in mental health care.